METTL14 Acts as a Potential Regulator of Tumor Immune and Progression in Clear Cell Renal Cell Carcinoma - Xu, Tianbo; Gao, Su; Ruan, Hailong; Liu, Jingchong; Liu, Yuenan; Liu, Di; Tong, Junwei; Shi, Jian; Yang, Hongmei; Chen, Ke; Zhang, Xiaoping (Frontiers in Genetics, 2021)
Clear cell renal cell carcinoma (ccRCC) is characterized by its insensitive to chemoradiotherapy and lacks effective diagnostic and prognostic biomarkers. In this study, we focused on the role of m6A RNA methylation regulators of tumor immune. Based on the expression of 20 m6A regulators, consensus clustering was performed to divide patients into cluster1/cluster2 and showed that there was survival difference between two clusters. Through cox regression analysis, five hub m6A regulators were screened to construct risk model. Further analysis showed that the risk score was an independent prognostic factor. GSEA, GSVA, and KEGG analysis revealed that immune cell pathways played a critical role between high risk group and low risk group. Combined with CIBERSORT and survival analysis, five hub tumor-infiltrating immune cells (TIICs) were identified for further study. Meanwhile, correlation analysis indicated that IGF2BP2 was positively associated with activated memory CD4 T cell and METTL14 was negatively correlated to regulatory T cell. Therefore, IGF2BP2 and METTL14 were regarded as key genes. Further study verified that only METTL14 possessed good diagnostic and prognostic value. Then, GSEA exhibited that METTL14 was mainly enriched in chemokine related pathway. We also found that CCL5 was obviously negatively correlated to METTL14 and might serve as a potential target of METTL14. In conclusion, these findings suggested that METTL14/CCL5/Tregs axis was a potential signaling pathway for regulating tumor immune, which might become novel therapeutic targets for ccRCC.